The role of sphingosine-1-phosphate in the tumor microenvironment and its clinical implications - Masato Nakajima; Masayuki Nagahashi; Omar M Rashid; Kazuaki Takabe; Toshifumi Wakai (Tumor Biology)
Elucidating the interaction between cancer and non-cancer cells, such as blood vessels, immune cells, and other stromal cells, in the tumor microenvironment is imperative in understanding the mechanisms underlying cancer progression and metastasis, which is expected to lead to the development of new therapeutics. Sphingosine-1-phosphate is a bioactive lipid mediator that promotes cell survival, proliferation, migration, angiogenesis/lymphangiogenesis, and immune responsiveness, which are all factors involved in cancer progression. Sphingosine-1-phosphate is generated inside cancer cells by sphingosine kinases and then exported into the tumor microenvironment. Although sphingosine-1-phosphate is anticipated to play an important role in the tumor microenvironment and cancer progression, determining sphingosine-1-phosphate levels in the tumor microenvironment has been difficult due to a lack of established methods. We have recently developed a method to measure sphingosine-1-phosphate levels in the interstitial fluid that bathes cancer cells in the tumor microenvironment, and reported that high levels of sphingosine-1-phosphate exist in the tumor interstitial fluid. Importantly, sphingosine-1-phosphate can be secreted from cancer cells and non-cancer components such as immune cells and vascular/lymphatic endothelial cells in the tumor microenvironment. Furthermore, sphingosine-1-phosphate affects both cancer and non-cancer cells in the tumor microenvironment promoting cancer progression. Here, we review the roles of sphingosine-1-phosphate in the interaction between cancer and non-cancer cells in tumor microenvironment, and discuss future possibilities for targeted therapies against sphingosine-1-phosphate signaling for cancer patients.